The Making of Transgenic Drosophila guttifera - Shittu, Mujeeb (Methods Protoc, 2020)
The complex color patterns on the wings and body of Drosophila guttifera (D. guttifera) are emerging as model systems for studying evolutionary and developmental processes. Studies regarding these processes depend on overexpression and downregulation of developmental genes, which ultimately rely upon an effective transgenic system. Methods describing transgenesis in Drosophila melanogaster (D. melanogaster) have been reported in several studies, but they cannot be applied to D. guttifera due to the low egg production rate and the delicacy of the eggs. In this protocol, we describe extensively a comprehensive method used for generating transgenic D. guttifera. Using the protocol described here, we are able to establish transgenic lines, identifiable by the expression of enhanced green fluorescent protein (EGFP) in the eye disks of D. guttifera larvae. The entire procedure, from injection to screening for transgenic larvae, can be completed in approximately 30 days and should be relatively easy to adapt to other non-model Drosophila species, for which no white-eyed mutants exist.